Surface wetting and contact angle: basics and characterisation - G. V. Beketov; O. V. Shynkarenko (Хімія, фізика та технологія поверхні, 2022)
Wettability is of pivotal importance in many areas of science and technology, ranging from the extractive industry to development of advanced functional materials and biomedicine problems. An increasing interest to wetting-related phenomena stimulates impetuous growth of research activity in this field. The presented review is aimed at the cumulative coverage of issues related to wettability and its investigation. It outlines basic concepts of wetting as a physical phenomenon, methods for its characterisation (with the emphasis on sessile drop techniques), and performances of contemporary instrumentation for wettability measurements.